RESEARCH OF PREDISPOSITION TO RISK OF PARTICIPANTS OF EXTREME SPORTS - Kuzikova, Svitlana; Shcherbak, Tetiana; Kuzikov, Borys; Blynova, Olena; Vavryniv, Olena; Khmiliar, Оleh; Popovych, Ihor (Revista Inclusiones, 2020)
The purpose of the research is a theoretical analysis and experimental study of predisposition to risk of participants of extreme sports and establishment of recommendations for the development of personal qualities for successful and safe activities. The study involved representatives of extreme sports (n = 180): skydivers (n = 60), base jumping representatives (n = 60) and motorcyclists (n = 60). The behavioral patterns of respondents engaged in extreme sports have been revealed and substantiated. Levels of predisposition to risk, self-confidence, nervous mental stability and search for thrills of representatives of motorcycle sports, parachuting and base jumping have been determined. The dynamics of the level of predisposition to risk, nervous mental stability and the scale of search for thrills depending on the experience of extreme activity of the respondents have been observed. The relationship between the level of predisposition to risk and such indicators as nervous mental stability, self-confidence, the search for thrills has been established (p ≤ .05). Recommendations for the development of the necessary personal qualities for successful extreme activities have been developed.